D4.7 Material from 4th workshop - ATHENA: Remote Sensing and archaeology: future and expectations - Hadjimitsis, Diofantos G.; Evagorou, Evagoras G.; Mettas, Christodoulos; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Nisantzi, Argyro; Themistocleous, Kyriacos; Schreier, Gunter; Krauss, Thomas; et al. (My University, 2018)
The specific deliverable summarizes the material related to the fourth workshop of the ATHENA project entitled as “ATHENA: Remote Sensing and archaeology: future and expectations”. The deliverable includes the overall agenda, the list of participants as well as the presentations carried out during the event. The minutes and the main outcomes of the workshop are also included in this report.
Keywords: ATHENA project; Remote sensing; Archaeology